A Method For Generating Plane Wave And Zero-Offet Vsp Synthetic Seismograms - Suprajitno Munadi (Scientific Contributions Oil and Gas, 1985)
Synthetic Vertical Seismic Profiles (VSP) seianograms are a useful aid to the interpretation of VSP re- conds, Plane wave VSP syntherics multiples and mode conversions can be computed rapldly n the frequency domain using a new recursive formulation. The method urilises the concept of "renultanz" phase related reflection and tranamission coefficients for a layer atack. High frequerncy signals can be handled with relative euse. The ability to control the order of the multiple avolds wraparound problems with the discrete Fourier transform. Several examples are used to lhustrate the method with relewance to seismic exploration.